Identification of CT Features to Differentiate Pulmonary Sarcoma from Carcinoma - Mohan, Supraja Laguduva; Dhamija, Ekta; Bakhshi, Sameer; Malik, Prabhat Singh; Rastogi, Sameer; Sheragaru Hanumanthappa, Chandrashekhara; Jain, Deepali; Pandey, Rambha (Indian Journal of Radiology and Imaging, 2024)
Background Primary lung sarcoma (PLS) differs in management protocols and prognosis from the more common primary lung carcinoma (PLC). It becomes imperative to raise a high index of suspicion on radiological and pathological features.Purpose The aim of this study is to highlight the variable imaging appearances of PLS compared with PLC, which impacts radiologic - pathologic correlation.Materials and Methods A retrospective observational study of 68 patients with biopsy-proven lung tumors who underwent baseline imaging at our tertiary care cancer hospital was conducted between January 2018 and March 2022. The patient details and imaging parameters of the mass on contrast-enhanced computed tomography (CECT) were recorded and analyzed for patients with PLS and compared with PLC. Follow-up imaging was available in 9/12 PLS and 52/56 PLC patients.Results Among 12 patients with PLS, 5 patients had synovial sarcoma on histopathology. PLS was seen in patients with a mean age of 40.8 years; the mass showed a mean size of 13.2 cm, lower lobe (75%), parahilar (75%), hilar involvement (41.7%), oval shape (41.7%), circumscribed (25%) or lobulated (75%) margins, lower mean postcontrast attenuation of 57.3 HU, fissural extension (50%), calcification (50%), and no organ metastasis other than to the lung. PLC (56 patients) was seen in the elderly with a mean age of 54.8 years; the mass showed a mean size of 5.7 cm, irregular shape (83.9%), spiculated margins (73.2%), higher mean postcontrast attenuation (77.3 HU), chest wall infiltration (30.4%), and distant metastasis (58.9%) at baseline imaging. A statistically significant difference (p < 0.05) was seen between sarcoma and carcinoma in the mean age, size, site, shape, margins, postcontrast attenuation, presence of calcifications, fissural extension, and distant metastasis.Conclusion The distinct imaging features of sarcoma help in differentiating it from carcinoma. This can also be used to corroborate with histopathology to achieve concordance and guide clinicians on further approach.
Keywords: lung neoplasms; carcinoma; sarcoma; synovial sarcoma; SYT–SSX fusion protein